**(1)** Solve the following system of equations for \(x\) and \(y\):

\[ 2x + 3y = 16 \]

\[ x – 4y = -3 \]

- (a) \( x = 2, y = 4 \)
- (b) \( x = 4, y = 2 \)
- (c) \( x = 3, y = 3 \)
- (d) \( x = 5, y = 1 \)

**(2)** Find the vertex of the quadratic function \( f(x) = x^2 – 6x + 8 \).

- (a) \( (2, -2) \)
- (b) \( (3, -1) \)
- (c) \( (1, 3) \)
- (d) \( (4, 0) \)

**(3)** If \( f(x) = 2x – 1 \) and \( g(x) = x^2 + 4 \), find \( (f \circ g)(2) \) (i.e., \( f(g(2)) \)).

- (a) \( 17 \)
- (b) \( 15 \)
- (c) \( 12 \)
- (d) \( 10 \)

**(4)** Simplify the expression:

\[ \frac{3x^3}{2x^2} \cdot \frac{4x^2}{6x} \]

- (a) \( \frac{x}{3} \)
- (b) \( 2x \)
- (c) \( \frac{4}{3}x \)
- (d) \( \frac{2}{3}x \)

**(5)** If \( f(x) = 2x + 1 \) and \( g(x) = x^2 – 3 \), find \( (g \circ f)(3) \) (i.e., \( g(f(3)) \)).

- (a) \( 14 \)
- (b) \( 11 \)
- (c) \( 10 \)
- (d) \( 7 \)